An educational leader's guide to curriculum mapping : creating and sustaining collaborative cultures - Hale, Janet A.; Dunlap, Richard F. (NU Curriculum., 2010)
Developed for district leaders, curriculum directors, principals, and teacher leaders, this book shows how to lead a collaborative and sustainable curriculum mapping initiative.